Comparison of different schedules of nocturnal home blood pressure measurement using an information/communication technology‐based device in hypertensive patients. Issue 11 (23rd October 2018) - Fujiwara, Takeshi; Nishizawa, Masafumi; Hoshide, Satoshi; Kanegae, Hiroshi; Kario, Kazuomi
Abstract : The objective of this study was to test our hypothesis that nocturnal home blood pressure (BP) measurement adapted to the chosen bedtime of participants (measurement at 2, 3, and 4 hour after the chosen bedtime) would be more reliable than measurement at fixed time points (2:00, 3:00, and 4:00 am ). Forty‐eight hypertensives were randomized to two groups undergoing two seven‐night measurement phases in a crossover manner and were asked to measure nocturnal home BP for 14 consecutive nights using a validated automatic information/communication technology‐based device. The intraclass correlation coefficients (ICCs) of systolic BP (SBP) obtained by a single measurement per night over two nights showed lower agreement than those of systolic BP obtained by multiple measurements based on a participant‐specified bedtime (0.539‐0.625 vs 0.675‐0.768) and multiple measurements at fixed times (0.468‐0.505 vs 0.661‐0.790). The ICCs obtained using specific bedtime‐based time points and those obtained using fixed time points showed major agreement when SBP was obtained by multiple measurements. The standard errors of measurement for SBP were similar between the bedtime‐based measurement phase (1.4‐1.7 mm Hg) and the fixed‐time measurement phase (1.2‐1.6 mm Hg). Neither a fixed bias nor a proportional bias was observed between the SBP values measured by the specific bedtime‐based time points and those measured by the fixed‐time measurement phase. In conclusion, the reliability of nocturnal home BP measurement appeared to be similar between nocturnal home BP adapted to the chosen bedtime of participants and that measured at fixed time points.